2008
DOI: 10.1128/iai.00161-08
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Ers Regulon of Enterococcus faecalis

Abstract: Ers has been qualified as the PrfA-like transcriptional regulator of Enterococcus faecalis. In a previous study we reported that Ers is important for the survival within macrophages of this opportunist pathogenic bacterium. In the present work we have used proteomic and microarray expression profiling of E. faecalis JH2-2 and an ers-deleted mutant (⌬ers mutant) strains to define the Ers regulon. In addition to EF_0082 (encoding a putative facilitator family transporter), already known to be under Ers regulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 45 publications
2
36
0
Order By: Relevance
“…The samples were analyzed with the CEQ8800 sequencing apparatus (Beckman Coulter). The determination of the DNA sequence of the protected region was carried out according to the method described by Riboulet-Bisson et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…The samples were analyzed with the CEQ8800 sequencing apparatus (Beckman Coulter). The determination of the DNA sequence of the protected region was carried out according to the method described by Riboulet-Bisson et al (2008).…”
Section: Methodsmentioning
confidence: 99%
“…Investigation of members of the Ers regulon showed that this reg-ulator directly interacts with the promoter regions of ers, ef0082, arcABC, and ef1459 (25). Sequence comparison of these regions allowed the characterization of a putative consensus sequence (AACATTTGTTG) that shows similarity to the PrfA box of Listeria (TTAACANNTGTTAA) (25).…”
mentioning
confidence: 99%
“…Ers plays an important role in the survival of oxidative stress and in the survival of the bacterium in mouse macrophages, as well as in the virulence of E. faecalis (6,25). Investigation of members of the Ers regulon showed that this reg-* Corresponding author.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…DNaseI Footprinting Analysis DNaseI footprinting analysis was performed according to the method described by Riboulet-Bisson et al 15) with some modification. The 5′ tvsod-ogg fragment was generated by PCR with pUC119-5′ tvsod-ogg as a template and a D4 dye end-labeled primer set of M13-20 (5′-D4-GTA AAA CGA CGG CCA GT-3′) and M13rev (5′-D4-GGA AAC AGC TAT GAC CAT G-3′).…”
Section: )mentioning
confidence: 99%